Voluntary Agreements and the Environmental Efficiency of Participating Farms - Andrea Ordó\~nez; Jutta Roosen (Kiel University, Department of Food Economics and Consumption Studies, 2003)
Voluntary environmental agreements have been popular with government agencies in several countries. However, many questions remain about their efficiency as a regulatory tool. Recent analyses suggest that they are more effective than classical regulatory or economic approaches when dealing with nonpoint pollution and when innovation processes at the source are necessary to define effective regulation. This paper applies an activitybased framework to assess the contribution of voluntary agreements to the environmental performance of farms participating voluntarily in a whole farm plan in the Southern part of Belgium. Using a cross-section of 52 farms, our results show that farms entering into environmental agreements are environmentally more efficient than non-participating farms when non-desirable outputs and the conservation of landscape features is accounted for in the analysis.
Keywords: Q12; Q2; C14; 330; Agri-environmental indicators; Data envelopment analysis; Environmental efficiency; Voluntary agreements; Whole farm plan; Landwirtschaft; Umweltschutz; Selbstverpflichtung; Technische Effizienz; Schätzung; Belgien